Correlation Between Calcium Phosphorus Product and Carotid Intimal-Medial Thickness in Patients of Chronic Kidney Disease Presenting to a Tertiary Care Hospital (Medical Forum Monthly, 2020)
Objective: To determine the correlation between Calcium Phosphorus product and carotid intimal-medial thickness in patients of chronic kidney disease presenting to a tertiary care hospital.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Nephrology, Shaikh Zayed Hospital Lahore from 29-10-2016 to 28-04-2017.Materials and Methods: One hundred and ten chronic kidney disease patients presenting to the Nephrology Unit of Shaikh Zayed Hospital Lahore. Patients were either gender, having age ≥30 years and ≤60 years with chronic kidney disease for at least 3 months. Patients fulfilling the inclusion and exclusion criteria were enrolled in the study. An informed consent was taken from the patients before including them in the study. Demographics of the patient which include name, age, gender, and carotid intimal-medial thickness was recorded. Blood samples for estimation of serum calcium and phosphorous were taken by using aseptic measures and standard procedure by the researcher himself and were sent immediately to the laboratory for serum analysis. Results were collected the next day by the researcher and Confidentiality of the data was ensured. Pearson correlation coefficient was calculated to measure the correlation between calcium phosphorus product and mean arterial pressure.Results: The mean age of the patients was 52.6±8.33 years. Gender distribution shows that 56.4% (n=62) were males while 43.2% (n=48) were females. The mean duration of chronic kidney disease (CKD) was 8.81 years. The mean calcium phosphorus product and carotid intimal medial thickness (CIMT) was 57.2±7.19 and 0.45±0.09 respectively. There was a positive correlation between calcium phosphorus product and CIMT with a Karl Pearson correlation coefficient of 0.671 with pvalue <0.001. Data stratified with regards to age, gender and duration of CKD.Conclusion: Calcium phosphorus product is positively correlated with carotid intimal medial thickness (CIMT) in patients with chronic kidney disease (CKD).